Moradia Estudantil - Martins, Natália de Oliveira (2015)
This study aims to develop the architecture project of a student housing in Rebouças district, in the city of Curitiba-PR, in order to supply part of the demand of installation and maintenance of students from other cities. The project adds spaces that promote the inclusion of the neighboring community in harmony to the primary use of student housing. At first, student housing is conceptualized, leading into account its historical, deployment types, spatial qualities relating to these spaces and its location in relation to the city. Then there is an approach of empty spaces in the city in order to take advantage of the existing infrastructure with the project implementation. The Rebouças district is then chosen for the project implementation because of its proximity to the center, with higher education institutions and the existence of some empty or underused spaces. It follows with a brief survey of the transformation of idle industrial construction processes with some examples of readjustment and reintegration of former industrial areas to the contemporary city. Finally, the design guidelines are established taking into account its urban integration, complementary uses that can provide and encourage integration with the community and thus creating an opening needs program towards the city.